POTENSI ANTIMIKROBIA KRIM EKSTRAK RANTING PATAH TULANG (Euphorbia tirucalli Linn.) TERHADAP Propionibacterium acnes ATCC 11827 DAN Candida albicans ATCC 24433 - Melina Scandinovita Setiorini; C.J. Soegihardjo; Kianto Atmodjo (Sanata Dharma University, 2014)
Abstract: Euphorbia tirucalli L. (Euphorbiaceae) or patah tulang has been used traditionally in Java fortreatment of fungal infections (Propionibacterium acnes causing acne and Candida albicans causingcandidasis). Information on their use is available, but scientific data on their bioactivity and safety ofactions still scanty. A study was conducted on the effect of organic extracts of this plant on fungal strains.Aceton extract were evaluated through the disc diffusion assay. Aceton extract was prepared by Soxhletapparatus for eight hours. Bacteria and yeast test strains were cultured on TSA (Trypthone Soya Agar)and on PDA (Potato Dextrose Agar) for Candida albicans. A 0.5 McFarland standard suspension wasprepared. Sterile paper discs 6 mm in diameter impregnated with 10 ml of the test extract (100 mg/ml)were aseptically placed onto the surface of the inoculated media. Thymol 0,5% and ketokonazol 2% wereused as standards. Discs impregnated with dissolution medium were used as controls. Activity of theextracts was expressed according to zone of inhibition diameter. Dimethylsulfoxide (DMSO) was used forpreparing test extracts (10, 20, 40, 60, 80, 100%) and were tested for Minimum Inhibitory Concentration(MIC) to Propionibacterium acnes and Candida albicans. MIC were obtained that 100% test extract wasgreatest and 10% test extract was weakest. Then, test extracts were prepared by concentrations 10, 9, 8, 7,6, 5%, and the result were the best were 10% test extract to Propionibacterium acnes and 6% test extractto Candida albicans. Antimicrobial test for pharmaceutical preparation, i.e. cream (o/w) were preparedusing 9 and 10% test extracts mixed with cream for testing to Propionibacterium acnes and 5 and 6% testextracts with cream for testing Candida albicans.The final results were 10% test extract had MIC toPropionibacterium acnes and 6% test extract had MIC in cream to Candida albicans.Keywords: Euphorbia tirucalli L., DMSO, Thymol, antimicrobial potency, cream (o/w), Propionibacteriumacnes, Candida albicans